INFLUENCE OF PANDEMIC ON TEACHER AND STUDENT PERFORMANCE AFTER COVID-19 PANDEMIC - Ilmas Uzza Abdul Aziz; Munawir Pasaribu (Proceeding International Seminar of Islamic Studies, 2022)
The outbreak of the Corona virus (Covid-19) that has hit most countries in the world has left humanity in deep sadness and anxiety. Social distancing or what is commonly referred to as social distancing or physical distancing has been designed in such a way as to reduce direct interaction between the wider community, because every individual has the potential to be a carrier or transmit the virus and even become an infected patient without symptoms. Performance is the result or output of a process. Mulyasa further said that performance can be defined as work performance, work implementation, work achievement, work results or performance. The results of this study indicate that the average teacher performance in teaching using the work from home system only reaches 50%. Overall, the performance results do not exceed the 70% limitKeywords:Teachers, Education, And Covid-19